10 YEARS OF LITHUANIA IN THE EU: HIGH EXPECTATIONS, LOW TRANSFORMATION? - KARMAZINAITĖ, SABINA; MANIOKAS, KLAUDIJUS; ŽERUOLIS, DARIUS (Politologija, 2015)
The subject of this article is changes in Lithuania during the EU membership period and the perception of them in the eyes of the elite and Lithuanian society. Therefore, in the first section the goal is to overview the main general changes in economics, society, and governance in 2004–2014 using various indicators and indexes. Although they reveal evident progress in economic convergence with the EU countries, also a higher level of tertiary education attainment, and longer healthy life years, they also show stagnation in long-term structural changes. Further, public policy development analysis states that despite the fact that after accession in 2004 there were opportunities to nationalize public policy agenda, it was still dominated by the EU related questions. Moreover, in comparison to pre-accession period, changes in public policy in Lithuania later were far lower. In the second section of the article the goal is to compare attitudes towards changes between Lithuanian elite members and Lithuanian society. Analysed data of the Lithuanian political elite survey showed that Lithuanian elite sees the biggest positive change during the period of 2004–2014 in public management and in implementing equal application of law principle. However, the article argues that Lithuanian society tends to evaluate the same changes rather differently and its attitudes are more pessimistic. Therefore, based on process tracing methodology, the authors explain how unfulfilled high economic expectations contributed to distrust of political institutions, high perception of corruption, low turnout, and migration. In addition, it is also argued that financial support of the EU stimulated state capture initiatives and corruption in Lithuania which also contributed to the pessimistic evaluations of changes by society.